Disturbed auditory perceptions: An Update - Egisto Molini; Ruggero Lapenna; Laura Cipriani; Maria Rita Del Zompo; Giorgia Giommetti; Giampietro Ricci (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
The search for tinnitus mechanisms is a speculative endeavour; a broad number of mechanisms may cause the tinnitus symptom and numerous tinnitus models have been proposed in recent years. There is no objective methods for detecting or evaluating the severity of tinnitus and severe tinnitus is usually defined as a tinnitus that interferes with sleep, work and social life. Patients, who exhibit a strong emotional reaction to tinnitus, a high level of anxiety, and psychosomatic problems, indicate that the limbic and autonomic nervous systems are crucial in clinically relevant tinnitus cases. Tinnitus is only one of the possible clinical aspects concerning disturbed auditory perceptions. The objective of this review was to organize all described disturbed auditory perceptions, with particular reference to the definition and the pathogenesis of a chronic bothersome tinnitus.